2020
DOI: 10.1101/2020.07.07.192237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age Influences on the Molecular Presentation of Tumours

Abstract: AbstractCancer is often called a disease of aging. There are numerous ways in which cancer epidemiology and behaviour change with the age of the patient. The molecular bases for these relationships remain largely underexplored. To characterize them we analyzed age-biases in the somatic mutational landscape of 12,774 tumours across 33 tumour-types. Age influences both the number of mutations in a tumour and their evolutionary timing. Specific mutational signatures are associated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…During the preparation of our manuscript, a study based on a similar concept has been released by Li et al 60 . In this work, Li et al used TCGA and the recent pan-cancer analysis of whole genomes data to study age-associated genomic differences in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of our manuscript, a study based on a similar concept has been released by Li et al 60 . In this work, Li et al used TCGA and the recent pan-cancer analysis of whole genomes data to study age-associated genomic differences in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the most common type of mutation in GBM is a C>T substitution, closely related to aging, and that mutational profiles of gliomas largely depend on the patient's age, e.g. there is association between EGFR-gains and loss of CDKN2A in GBM and mutations in ATRX in LGG (4). The inability of cells to repair damaged DNA is believed to be a major cause of aging (112), which further supports the strong position of age as a prognostic factor.…”
Section: Biomarkers Of Survivalmentioning
confidence: 99%
“…There is no doubt that cancer is a disease with a genetic background. The profiles of genetic alterations, e.g., point mutations, amplifications, losses of genetic material or fusions of genes, along with epigenetic modifications of the genome are cancer signatures (3,4). These aberrations often target protooncogenes, which promote cell proliferation but if mutated lead to uncontrolled proliferation of cells.…”
Section: Introduction Cancermentioning
confidence: 99%
“…Previous studies demonstrated that there are important molecular differences when considering the age of cancer patients (15,(31)(32)(33). Then, considering that perhaps the loss of tissue identity occurs in ageing, we tested the hypothesis that the patient's age influences the pattern of expression of specificity genes.…”
Section: Age Does Not Influence the Loss Of Tissue Specificity In Cancermentioning
confidence: 99%